Gas Leakage Detection System Using Arduino and GSM Module Review (International Journal of Communication Systems and Network Technologies, 2024)
In this paper, we propose the development of a Gas Leakage Detection System utilizing Arduino microcontroller technology and a GSM module for real-time alerting. The system aims to enhance safety measures by promptly identifying and notifying users about the presence of potentially hazardous gas concentrations. The core components include an Arduino board, a Gas sensor module (MQ series), and a GSM module (SIM900). The gas sensor continuously monitors the ambient air for gas concentrations, and when levels surpass a predefined threshold, an alarm is triggered. Simultaneously, the system utilizes the GSM module to send an alert via SMS to predefined mobile numbers, providing instant notifications to relevant stakeholders. The Arduino code orchestrates the functionality, with provisions for adjusting sensitivity thresholds and incorporating safety features such as a buzzer and LED indicators. The integration of SoftwareSerial enables communication with the GSM module. This Gas Leakage Detection System holds applications in various environments such as homes, industrial settings, and laboratories where early detection of gas leaks is crucial for preventing accidents and minimizing risks. The modularity of the system allows for scalability and adaptation to different gas sensors or communication modules. By implementing this system, we contribute to the advancement of safety technology, offering a cost-effective and efficient solution for gas leak detection and timely alerting. The project serves as a foundation for further enhancements and integration with smart home or industrial automation systems.
Keywords: Arduino; GSM Module; MQ Series Sensor; Gas Leakage Detection; SIM900; Gas Sensor; SMS Alert System; Buzzer; Industrial Safety